THE EFFECT OF TEACHING MODEL AND SELF EFFICACY TOWARD LEARNING ACHIEVEMENT OF ECONOMIC - Heni Oktalia; Johanes Sapri; Turdjai Turdjai (UNIB Press, 2017)
The objectives of this research was to investigate the interaction between teaching model and self-efficacy toward economic learning achievement of students. The design of this research was quasi experiment. The population of this study were 198 students of class XI IPS from 7 MA in Bengkulu Tengah, and 50 students as sample taken by purposive sampling. The data collected by questionnaire and a test of learning achievement of economic. The data analyzed by two way factorial analysis technique, and advance test by Tuckey-test. The result revealed that: students learning achievement of economic who were taught with Non-directive aided multimedia were higher than students those taught directive without multimedia; students learning achievement of economic with high self-efficacy were higher than students those with low self-efficacy; there were interaction between teaching model and self-efficacy of students learning achievement of economic; students learning achievement of economic with high self-efficacy higher if they were taught with Non-directive aided multimedia; and students learning achievement of economic with high self-efficacy higher if they were taught with directive without multimedia. Key words: non-directive teaching model, self-efficacy, students learning achievement of economic